Multipath inter-domain routing for named data networking - Xiao-yan HU; Jian GONG (Tongxin xuebao)
To facilitate content retrieval among NDN domains,a multipath inter-domain routing for named data networking(MIRNDN)was proposed.Under MIRNDN,an AS(autonomous system)maintained merely the routing state of content reachable from its own network or from its customers’ networks and aggregated routing information to mitigate routing scalability issue; “valley free”routing policy was applied to guide Interest packets that solicit content unreachable from the AS’s own network nor from its customers’ networks to explore matching data packets via multiple paths,and NDN’s requests aggregation,in-network caching and adaptive forwarding optimized such exploration; the reachability information of content from multiple paths was collected to support Interest multipath forwarding.The properties of FIB size and the convergence time and communication cost of routing update under MIRNDN were analyzed in theory.The experimental results in the AS level topology of current Internet validates that MIRNDN mitigates the scalability issue of NDN inter-domain routing,has relative short convergence time and moderate communication cost for routing update,and effectively reduces unnecessary Interest forwarding.